Because both of the equations = s, we can set them equal to each other.
c + 7 = 2c - 13. Now we can solve for c. Once you have found c, you can substitute it back into either of the two original equations and solve for s.
Compare both sides,
x² - x - 1 = 2 - 3x
x² + 2x - 3 = 0
x² -x + 3x - 3 = 0
x(x - 1) 3(x - 1) = 0
(x - 1)(x+3) = 0
x = 1 or - 3
In short, Your Answers would be 1 & -3
Hope this helps!
That already is a 91.1 grade average. If you want to keep that, get a 90 and above. To find your average, add all your test scores up and divide them by how many scores there are. For instance if you add all those scores up you get 274. Divide it by 3 because there are three scores and there is your average!
Answer:
x^(5/6) + 4(x^(7/3))
Step-by-step explanation:
Simplify x to the 1/3 power MULTIPLIED BY (x to the 1/2 power + 2x to the 2 power )
Simplify x^(1/3) × (x^(1/2) + (2x)^2)
= x^(1/3)(x^(1/2)) + x^(1/3)((2x)^2)
= x^(1/3+1/2) + 4(x^(1/3+2))
= x^(5/6) + 4(x^(7/3))
x^(1/3) is y such that y^3 = x
(x^(1/3) × x^(1/3) × x^(1/3)) = x^(1/3+1/3+1/3) = x^1 = x
x^(1/2) = √2 = y such that y^2 = x
(2x)^2 = 4x^2